2016
DOI: 10.3906/kim-1502-95
|View full text |Cite
|
Sign up to set email alerts
|

Durability of carbon/conducting polymer composite supported Pt catalysts prepared by supercritical carbon dioxide deposition

Abstract: Polypyrrole (PPy)/carbon (C) composites were synthesized by oxidative chemical polymerization and used as support material for Pt nanoparticles. PPy/C supported Pt nanoparticles were prepared by using a promising catalyst preparation method, supercritical carbon dioxide (scCO 2) deposition. The prepared materials were characterized by using BET, TGA, XRD, and TEM techniques. Cyclic voltammetry was used in order to determine the electrocatalytic activity of the prepared catalyst for hydrogen oxidation and oxyge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 15 publications
1
8
0
Order By: Relevance
“…The strong bands at 1208 and 1269 cm −1 are attributed to SO 2 , and a strong absorption peak at 1026 cm −1 most probably belongs to  SO3[H + ]. The formation of a peak at around 3170 cm −1 shows the protonation of the triazole rings, in addition to the broad peaks around 3500 cm −1 . Similar absorption bands were also present in FTIR spectra as shown in Supporting Information Figures S2 and S3.…”
Section: Resultssupporting
confidence: 64%
“…The strong bands at 1208 and 1269 cm −1 are attributed to SO 2 , and a strong absorption peak at 1026 cm −1 most probably belongs to  SO3[H + ]. The formation of a peak at around 3170 cm −1 shows the protonation of the triazole rings, in addition to the broad peaks around 3500 cm −1 . Similar absorption bands were also present in FTIR spectra as shown in Supporting Information Figures S2 and S3.…”
Section: Resultssupporting
confidence: 64%
“…The integrated hydrogen adsorption and desorption areas of the CV curves provide an estimation of ECSA, which is directly related to the electrooxidation activity of the catalysts. However, the large capacitive current due to double layer charging, made the determination of ECSA extremely difficult, but still, from the average area of hydrogen adsorption/desorption peaks [86–89], the ECSA of Pt/rGO (DMF) and Pt/rGO (HYD) catalysts (in case of fresh electrode) were calculated to be 28.1 and 18.2 m 2 g −1 , respectively. The obtained results showed that the Pt/rGO (DMF) exhibited higher activity than the Pr/rGO (HYD).…”
Section: Resultsmentioning
confidence: 99%
“…The asymmetric and symmetric stretching modes of the CF 3 moiety show up at 1,210 and 1,164 cm -1 . As well, the bands appearing at 632 and 512 cm -1 can be assigned to the anion, caused by the symmetric and asymmetric deformation vibration of the SO 3 moiety [18][19][20]. Thus, only the remaining bands at 573, 728, 910, 1,354, and 1,469 cm -1 are most probably caused by vibration modes of the cation.…”
Section: Uptake Of Pils By M-pbi By a Swelling Processmentioning
confidence: 87%